2020
DOI: 10.1101/2020.10.24.20218701
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical and spatial characteristics of Severe Acute Respiratory Syndrome by COVID-19 in Indigenous of Brazil

Abstract: The indigenous people of Brazil present several cases and deaths, affecting 158 peoples, with high vulnerability and limited access to health services. The objective is to investigate the clinical characteristics of severe acute respiratory syndrome by COVID-19 in indigenous peoples of Brazil. The epidemiological study, descriptive, from the data of the platform opendataSUS referring to the SIVEP-GRIPE in the period 01/01/2020 until 31/08/2020. Profile variables, signs and symptoms, and risk/comorbidities fact… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Being corroborated by the study (Sardinha, Lima, et al, 2021) which identified chronic heart diseases (18.97%) and diabetes (18.97%) among the most prevalent comorbidities in the indigenous population with SARS due to COVID-19.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Being corroborated by the study (Sardinha, Lima, et al, 2021) which identified chronic heart diseases (18.97%) and diabetes (18.97%) among the most prevalent comorbidities in the indigenous population with SARS due to COVID-19.…”
Section: Discussionmentioning
confidence: 65%
“…Similarly, in a study conducted in Brazil with 472,688 severe cases, the independence test was highly significant in vaccinated survivors (<0.0001), and the binary regression showed an odds ratio almost twice as high for invasive ventilation, admission to the hospital. ICU and death in unvaccinated cases (Sardinha, Lobato, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Source: Sardinha, 2021 [11] The study did not require Research Ethics Committee (REC) approval because we analyzed public and universal open access data. The data are in aggregated format and do not contain personal data of the patients.…”
Section: Fig 1 Regions and Federation Units In Brazilmentioning
confidence: 99%
“…Typical changes in chest High Resolution Computed Tomography of COVID-19 patient: Peripheral, bilateral, Ground Glass Opacification with or without consolidation or visible interlobular lines ("web like" or "crazy paving") Multifocal Ground Glass Opacification of rounded morphology with or without consolidation or visible intralobular lines ("web like" or "crazy paving") Reverse halo sign or other findings of organizing pneumonia [28] [29]. V. CONCLUSION In this paper, we presented the functioning and viable applications of medical imaging.…”
Section: Detecting Covid-19 In Lungsmentioning
confidence: 99%